2020
DOI: 10.1039/d0cb00108b
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the enthalpic contribution of hydrogen bonds by solvent shielding

Abstract: Altering local dielectric properties induced by solvent shielding, enhances polar interactions and leads to enthalpically driven recognition of polar substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…This increase in the enthalpic attraction between the subunits can be correlated to the role of the inner hydrophobic polymer layers in shielding the backbone hydrogen bonding sites from competitive water molecules. In their study on the binding between mannoside ligands and lectin, Cramer et al reported a −13 kJ mol –1 enthalpic contribution that was a direct consequence of H-bond shielding . In contrast, it was found that when the hydrogen bond network in the binding site was disrupted, the enthalpic benefit was completely abolished.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in the enthalpic attraction between the subunits can be correlated to the role of the inner hydrophobic polymer layers in shielding the backbone hydrogen bonding sites from competitive water molecules. In their study on the binding between mannoside ligands and lectin, Cramer et al reported a −13 kJ mol –1 enthalpic contribution that was a direct consequence of H-bond shielding . In contrast, it was found that when the hydrogen bond network in the binding site was disrupted, the enthalpic benefit was completely abolished.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, it was found that when the hydrogen bond network in the binding site was disrupted, the enthalpic benefit was completely abolished. Shielding of H-bonds by hydrophobic entities has also been reported to strengthen the H-bonds as they provide low dielectric environments in which dipole–dipole “electrostatic” interactions are stabilized. Importantly, simulation research by Barril and co-workers suggested that the level of shielding, and hence the influence on enthalpic contributions, is likely proportional to the hydrophobic quantity …”
Section: Resultsmentioning
confidence: 99%
“…The ITC results indicate that the interaction was favorable in terms of enthalpy and entropy, with a calculated ΔG 0 of −6180.92 kJ mol −1 , mainly driven by the exothermic component of the binding, with a ΔH 0 of −5722 ± 120.4 kJ mol −1 and a ΔS 0 of 1.54 kJ mol −1 . Both parameters suggest that the interaction between Aux1 pLS20 and Rel pLS20 is strongly affected by hydrogen bond formation and van der Waals interactions [49] . The entropy component, although small, may be related to the burial of water-accessible surface area upon binding, resulting in the release of interfacial water molecules to the solvent, contributing favorably to the total entropy of interaction [50] .…”
Section: Resultsmentioning
confidence: 99%
“…Differential scanning calorimetry (DSC) results of liquid crystals even for those produced through supramolecular assemblies usually possess relatively high enthalpy changes (ΔH) accompanied with the crystalline mesomorphic transitions (∼20-100 kJ/mol) (Tsuji et al, 1979) (Yousif and Al-Hamdani, 1993) (Domalski and Hearing, 1996) Morsy, 1999) (2000) (Chidichimo et al, 2004) (Acree and Chickos, 2006). However, few examples have been reported in the literature where the ΔH values of melting are lower than 10 kJ/mol (Du et al, 2019) (Cramer et al, 2020) (Huang et al, 2020) (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%